Alternatives to Petroleum-Based Containers for the Nursery Industry - Gary W. Knox; Matthew Chappell (EDIS, 2011)
Biodegradable containers are an increasingly attractive option for consumers and growers alike. This 5-page fact sheet looks at the past, present, and future of containers used in container nursery production. Written by Gary W. Knox and Matthew Chappell, and published by the UF Department of Environmental Horticulture, November 2011.